THE RELATION OF CONCENTRATION TOWARDS THE JAPANESE LANGUAGE LISTENING SKILLS ON STUDENTS OF RIAU UNIVERSITY - Merri Silvia Basri; Zainal Rafli; Fathiaty Murtadho (English Education Department, 2020)
The aim of this study is to find out the relationship between concentration and Japanese listening skills. This research is conducted on Japanese language students at Riau University. The research method used in this study was quantitative approach, survey methods with measurement and test techniques, while the analysis technique used was path analysis approach. The population of the target population was all fourth semester Japanese language students at Riau University, which are 52 students. The sampling was done with total sampling techniques. The relationship between concentration and Japanese listening skills is 0.309. It is concluded that: There is a positive relation between concentration and listening skills in Japanese language of Riau University students.